"Walking in Two Worlds": Toward an Indigenist Ecological Systems Model for Group Therapy. (July 2022) - Fish, Jillian; Hirsch, Glenn; Syed, Moin
Walking in two worlds is a common metaphor Indigenous peoples use to describe their experiences navigating the differences between Indigenous and Western epistemological and ontological worldviews across various contexts. Despite wide support for this phenomenon, there have been few attempts to address Indigenous–Western cultural incongruities through structural changes in counseling psychology, although as a profession, it is well equipped to do so. Thus, we propose for counseling psychology to move toward the Indigenist ecological systems model (IESM) as an integrative framework for promoting Indigenous epistemologies and ontologies in science and practice. We provide a brief overview of IESM and a direct application of the model through a case illustration of Walking in Two Worlds, a psychotherapy group for Indigenous peoples. With IESM, we describe creating an Indigenous-informed clinical intervention that leverages Indigenous epistemologies and ontologies, prompting real ecological change. We conclude with implications IESM has for counseling psychology.